Management of an Unusual Orbitocranial Penetrating Injury - Han Y. Yin; Swetha Dhanireddy; Alexander E. Braley (Case Reports in Ophthalmological Medicine)
Background. An intraorbital injury with a blunt penetrating intraorbital foreign body (IOFB) is an unusual cause of penetrating trauma. This type of trauma is considered a surgical emergency given the risk to vision in addition to potential intracranial injuries such as vascular injury, dural laceration, and neurologic injury. A thorough history and physical exam, along with careful radiographic and multidiscipline intervention, is crucial in providing the patient the most appropriate care. Case Presentation. A 66-year-old male presented to the emergency room (ER) after falling down the stairs and suffering an orbitocranial penetrating injury. He underwent urgent fluoroscopy-guided foreign body removal with a multidisciplinary team after a workup revealed no significant ocular or intracranial injuries. The foreign body was removed with an anterior approach without any complications. Conclusion. In this study, we demonstrated that IOFB in proximity to orbitocranial structures requires a careful multidisciplinary team approach. An interventional radiology- (IR-) guided approach in extracting the foreign body is essential to prevent further injury. A high dose of intravenous steroid was not used due to initial suspicion of intracranial involvement. Prompt removal decreased risk of further vision loss.